Synthesis and characterization of structural and magnetic properties of graphene/hard ferrite nanocomposites as microwave-absorbing material - Durmus, ZEHRA; Durmus, Ali; Kavas, Huseyin (My University, 2015)
In this study, barium hexaferrite nanoparticles were synthesized via the citrate sol-gel combustion method in a reaction medium consisting of various forms of graphene nanosheet, such as expanded graphite, expanded graphite oxide, and reduced graphite oxide to prepare novel type graphene/hexaferrite nanocomposites as microwave-absorbing material. The microstructural features and physical properties of nanocomposites were characterized by X-ray diffraction, Raman spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and thermogravimetric analysis methods. Magnetic properties of the nanocomposites were studied by a vibrating sample magnetometer, and the microwave-absorption and -reflection properties of samples were also determined in the frequency range of 8-12 GHz. It was found that the surfaces of the graphene nanosheets were successfully decorated with the barium hexaferrite nanoparticles, and the resulting layered nanocomposite structure showed the reflection loss value of -58 dB at 11.42 GHz.